Research Capability of Teachers: Its Correlates, Determinants and Implications for Continuing Professional Development - Caingcoy, Manuel (Journal of World Englishes and Educational Practices, 2020)
Recently, research capability has received an overwhelming and remarkable interest among academics and practitioners. This is timely since the Department of Education had institutionalized research and encouraged teachers to engage in it to support evidence-based practice, decision-making, policy, and program development. On these premises, a study was carried out to assess the research capability of public teachers in Malaybalay City, determine its correlates and determinants. It utilized descriptive, correlational, and explanatory designs. It administered survey questionnaires to 92 participants. Data were analyzed using descriptive and inferential statistics. The results revealed that teachers were slightly capable of conducting research and having neutral attitudes toward it, motivated to write research, had a high level of difficulties in research processes, and moderately capable of action planning. They also show evidence of potential in mentoring. Further, mentoring and action planning skills, motivation to write research, attitudes toward research, and the number of studies completed by teachers were the correlates of their research capability at different magnitudes of the relationship. Notably, the research capability of teachers had a low, negative but significant relationship with their age and accumulated years of service. Thus, this capability deteriorates as they age and accumulate years of service. The motivation to write research, the number of studies completed, and age were the determinants of research capability. It was concluded that research capability can be determined and predicted by how motivated teachers are to write research, how productive they are in research, and how young they are when they engage in this rigorous endeavor. The study identified and recommended topics for continuing professional development.